Kiai's Leadership in Instilling a Culture of Tasamuh in Modern Islamic Boarding Schools in Riau Islands - Husnullail, Muhammad; Kasful Anwar; Mahmud MY (International Journal of Education, Language, and Social Science, 2025)
This research aims to find out several aspects, namely: 1) What is the Kiai's leadership in instilling Tasamuh cultural values, 2) Implementation of instilling Tasamuh cultural values, 3) What obstacles do Kiai experience in Islamic boarding schools and 4) Implications of cultivating Tasamuh cultural values in Islamic boarding schools. The research method used is a qualitative approach with case studies. The data collection process involved interviews, observation, and document analysis. Data analysis was carried out through the steps of data condensation, data presentation, and drawing conclusions. Data validity was tested through the credibility, dependability and certainty of the data. The results of the research reveal several things, including: first, Kiai carry out their role as leaders with two leadership patterns, namely: Personal and Collective Leadership, Second, Implementation with the Kyai Exemplary strategy, Learning Classical Books, Collaboration with uswatun hasanah, Internalisation of Tasamuh values and General Amaliyah. Third, the obstacles experienced by kiai and fourth, the implications of Tasamuh cultural values